(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This conceptual paper isbased on the scope of entrepreneurship in India. The Prime objective of thisstudy is to find out the areas where India excels in providing opportunities tonew entrepreneurs. As India has second largest population in the world, itsneed of an hour is to provide employment in new and innovative ways. This paperprovides an insight study of the sectors in which there is purview forentrepreneurship. The paper also focuses on prospects for Indian entrepreneurs.There exists innumerable business opportunities in the environment. Forunleashing by the entrepreneurs. On the basis of this paper some suggestionsare given in order to encourage and promote entrepreneurship in India.